Local governance and community development the case of the Iloilo City barangays - Hernando, Christine Mae D. (2004)
Ten years after the implementation of the Local Government Code of 1991, a number of studies were conducted to assess the process of democratic local governance. However, most of such studies were focused on the higher levels of the local government system, while scant attention was given to governance at the grassroots. This paper discusses findings of the study on local governance and community development in the selected barangays of Iloilo City. The study conducted in 2003, presents the practices, problems, and challenges of local governance and community development at the level of the barangays. It also presents recommendations in the area of policy and human resource development, and research to make local governance more responsive to barangay development.
Keywords: Community development; Community development -- Iloilo; Local governance -- Iloilo City